Factores socioculturales y estado nutricional de niños pre escolares de las Instituciones Educativas Iniciales del Centro Poblado San Martín de Porres - San José, 2010 - Monsefú Quiroz, Ruth Maribel (2010)
The present work of investigation, of descriptive type correlacional and transverse court, carried out with pre-school children and his mothers of four Institutions of Initial Education of the Populated Center Porres's Minor St Martin - San Jose, 2010, with the intention of determining the relation between the sociocultural factors: Economic familiar revenue per capita, type of family, degree of instruction and level of information of the mother on nutrition and, the nutritional condition of the pre-school one. The sample was constituted by 120 pre-school ones and his mothers. For the compilation of information one used two instruments: A test on sociocultural factors elaborated by the authoresses to recognize and the tables of growth of the World Health Organization to identify the nutritional condition of the preschool ones. The statistical analysis of the results I realize by means of the test of independence of criteria chi square x2. Coming to the following results: In relation to the sociocultural factors, according to the economic familiar revenue per capita the majority of families (86.7 per cent) were in situation of poverty; of which 57.5 per cent they were extreme poor and 29.2 poor persons. The type of predominant family was the nuclear one (75.8 per cent). The major percentage (38.3 per cent) of the mothers of the school pre presented degree of primary instruction and 10 per cent no degree of instruction, the level of information about supply of the school pre in the main was good (54.2). In the nutritional condition of the pre-school ones, one thought that 74.2 per cent they were eutrophic, 15.83 per cent chronic malnutrition and 10 per cent overweight. Significant relation found between the factors degree of instruction and level of mother information about supply and the nutritional condition of the pre-school one (p <0.05). Statistically significant relation did not meet between the variables corresponding to the familiar revenue per capita and the type of family the children's nutritional condition pre school.